2018
DOI: 10.1007/s41095-018-0113-0
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous foveated preview for progressive Monte Carlo rendering

Abstract: Progressive rendering, for example Monte Carlo rendering of 360• content for virtual reality headsets, is a time-consuming task. If the 3D artist notices an error while previewing the rendering, they must return to editing mode, make the required changes, and restart rendering. We propose the use of eye-tracking-based optimization to significantly speed up previewing of the artist's points of interest. The speed of the preview is further improved by sampling with a distribution that closely follows the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Ray tracing was used to render the foveal region and rasterization to render the peripheral region. To speed up previewing the artist's points of interest, Koskela et al [119,124] applied foveated rendering to progressive Monte Carlo rendering, which omits more than 90% of rays that must be traced in real time. Their user study demonstrated that the perceived convergence of the proposed method was 10× faster than that of a conventional preview, and participants rated the method to have only marginally more artifacts in areas where it had to start rendering from scratch.…”
Section: Multi-spatial Resolution Based Ray Tracingmentioning
confidence: 99%
“…Ray tracing was used to render the foveal region and rasterization to render the peripheral region. To speed up previewing the artist's points of interest, Koskela et al [119,124] applied foveated rendering to progressive Monte Carlo rendering, which omits more than 90% of rays that must be traced in real time. Their user study demonstrated that the perceived convergence of the proposed method was 10× faster than that of a conventional preview, and participants rated the method to have only marginally more artifacts in areas where it had to start rendering from scratch.…”
Section: Multi-spatial Resolution Based Ray Tracingmentioning
confidence: 99%
“…We use an inversion method [48] to determine the sampling distribution in polar space. Equation 1 is the PDF that simulates VAE described in [49] with an adaption on the circumference of concentric circles [30]:…”
Section: Visual Acuity Eccentricitymentioning
confidence: 99%